Perception of food delivery rider during movement control order (MCO): a case study in Wangsa Maju Kuala Lumpur / Nurul Ain Nazihah Mohd Ikbal, Alias Abdullah and Syakir Amir Ab Rahman - Mohd Ikbal, Nurul Ain Nazihah; Abdullah, Alias; Ab Rahman, Syakir Amir (Universiti Teknologi MARA, 2022)
Food delivery service in Malaysia is an emerging trend in urban settings prior to 2020 or the COVID-19 pandemic. During the implementation of Movement Control Order (MCO) by the Malaysia government to control the spread of COVID-19 virus, food delivery service was listed as an essential service that was allowed to operate while dine-in at food outlets were prohibited. This study aims to investigate the needs of food delivery services in an urban planning to facilitate during and after COVID-19 pandemic. Wangsa Maju Kuala Lumpur was selected as the case study. This study was conducted on 100 food delivery staffs from Grab Food and Food Panda delivery platform through purposive sampling. Data were collected by questionnaire survey and were analyzed by SPSS software. The findings demonstrated that there were three themes of challenges which are (i) no waiting and resting area, (ii) inadequate and unavailability of parking spaces, and (iii) delivery location issue. The findings served as a platform for future study as well as the development of policy and guidelines together with collaboration planning to improve urban management.